The evolution of the Italian novel (based on the works of Clorinda Di Fini), part 2 - A.A. Katorova; Y.S. Boronenkova (Язык и текст, 2017)
The article deals with the evolution of the Italian novel in different literary and historical periods, starting with the epic poem of Antiquity up to the historical novel (“The Betrothed” by Alessandro Manzoni) and the social novel (“The House by the Medlar-Tree” and “Mastro-don Gesualdo” by Giovanni Verga). Based on the works of Italian philologist Clorinda Di Fini, the article shows how the focus of narrative shifts from the fate of the upper classes to the lives of ordinary people in a larger historical context, as well as the author's position in the novel moves towards impersonality and objective reflection on social problems.